Relationship Between Skin Hydration Levels With The Severity of Diaper Dermatitis in Children Aged 0-24 Months - Widya Gabriella Manurung; Deryne Anggia Paramita; Kristo A. Nababan (Eduvest - Journal of Universal Studies, 2025)
Diaper dermatitis is a common dermatological condition in children, particularly those aged 0-24 months, characterized by mild to severe inflammation. Over hydration skin has been associated with the occurrence of diaper dermatitis, as it can disrupt the skin barrier and trigger inflammation. To determine the relationship between skin hydration levels and the severity of diaper dermatitis in children aged 0-24 months. A cross-sectional study was conducted on 87 children aged 0-24 months with diaper dermatitis. Skin hydration levels were measured using a Corneometer® CM 825. The severity of diaper dermatitis was assessed using the Buckley Scale. Data analysis used the Chi-Square test, and results were considered significant if p<0,05. The relationship between the level of skin hydration and the severity of diaper dermatitis showed significant results (p=0.034) where the majority of subjects had a sufficiently hydrated degree of skin hydration in the diaper area, which was 69 people. Skin with sufficiently hydrated has a higher risk of more severe diaper dermatitis.